A study of the mobility of mainland students: Factors and issues behind pursuing a teacher education program in Macau. Issue 2 (30th August 2019) - Wong, Ping Man; Cheung, Alan; Yuen, Wai Wa
Abstract : Purpose: The purpose of this paper is to contribute to a better understanding of the international mobility of mainland students in special administrative regions of China and in places outside China. Design/methodology/approach: There have been studies using the framework of push–pull and reverse push–pull factors to explore the movement of mainland students to North America, Australia, Singapore and Hong Kong. This study follows up by exploring such research directions in Macau, which is another special administrative region of China. Different from previous studies, the sample of this study came specifically from 130 students enrolling in teacher education undergraduate programs in Macau. Findings: In this study, using data collected from questionnaires and interviews, the factors affecting mainland student teachers' choice of Macau as a place for their undergraduate studies are examined. Other related issues such as the challenges these students face and their intentions after their graduation are also studied. Originality/value: The data collected for this study were primary and original, drawing specifically from students enrolling teacher education programs. Following the various studies on the global movement of mainland students, this study aimed at understanding mainland students' mobility pattern in one of China's special administration regions, Macau. In this regard, cultural identity and cultural factors were considered on top of other factors.